2015
DOI: 10.1088/0967-3334/36/7/1399
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene fluoride sensor-based method for unconstrained snoring detection

Abstract: We established and tested a snoring detection method using a polyvinylidene fluoride (PVDF) sensor for accurate, fast, and motion-artifact-robust monitoring of snoring events during sleep. Twenty patients with obstructive sleep apnea participated in this study. The PVDF sensor was located between a mattress cover and mattress, and the patients' snoring signals were unconstrainedly measured with the sensor during polysomnography. The power ratio and peak frequency from the short-time Fourier transform were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This spectral profile is in line with our previous study [32] where a similar power spectrum density (PSD) was found when comparing snoring and normal breathing PSDs. It is also consistent why power ratios perform well in certain SN profiles [44]. However, not all snores had the same spectral profile; Fig.…”
Section: A Source Separation Of the Emfit Signalsupporting
confidence: 71%
See 3 more Smart Citations
“…This spectral profile is in line with our previous study [32] where a similar power spectrum density (PSD) was found when comparing snoring and normal breathing PSDs. It is also consistent why power ratios perform well in certain SN profiles [44]. However, not all snores had the same spectral profile; Fig.…”
Section: A Source Separation Of the Emfit Signalsupporting
confidence: 71%
“…However, in our experiments, several SN profiles did not contain spectral components only in this band. Another study performed with PVDF sensors by Hwang et al used a power ratio between components above and below 10 Hz [44]. Judging from the results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flexible sensors can be developed by microfabrication process [34,35,36,37,38], textile weaving [39,40], or commercial materials [41]. The sensors are adapted for snoring detection system [41], mobility pattern research of a person on a bed [42], human motion sensing [43,44], and real-time health and fitness monitoring [45]. …”
Section: Introductionmentioning
confidence: 99%